Low resistive Au-free, Ta-based, recessed ohmic contacts to InAlN/AlN/GaN heterostructures. (October 2015) - Bergsten, J; Malmros, A; Tordjman, M; Gamarra, P; Lacam, C; di Forte-Poisson, M-A; Rorsman, N
Abstract The formation of recess etched Au-free ohmic contacts to an InAlN/AlN/GaN heterostructure is investigated. A Ta/Al/Ta metal stack is used to produce contacts with contact resistance (Rc) as low as 0.14 Ω mm. It is found that Rc decreases with increasing recess depth until the InAlN barrier is completely removed. For even deeper recesses Rc remains low but requires annealing at higher temperatures for contact formation. The lowest Rc is found for contacts where the recess etch has stopped just above the 2D electron gas channel. At this depth the contacts are also found to be less sensitive to other process parameters, such as anneal duration and temperature. An optimum bottom Ta layer thickness of 5–10 nm is found. Two reliability experiments preliminary confirm the stability of the recessed contacts.